(untitled) (Global Journal of Science Frontier Research, 2014)
In this paper, we discuss about the recently collected sample of ground water at different locations in Uttar Pradesh State of India and its experimental analysis in laboratory for the presence of Oxygen content. Also, we represents the data graphically and interpreted the data using the method called analysis of variance. Further, we analyze our findings with the established results. Lastly we concluded that the samples depend on location as well as month also that is in different months and different areas disolved Oxygen are different.